Combined Cellular Blue Nevus and Trichoepithelioma - Martin, Richard (Matrix Medical Communications, 2013)
Biphasic lesions composed of melanocytic and epithelial components are not uncommon. Combined trichoepithelioma and cellular blue naevus is a rare lesion that may mimic melanoma clinically. The authors describe what they believe to be the fourth case of this rare tumor and review the literature. Recent descriptions of malignant basomelanocytic tumors have raised interesting questions surrounding the pathogenesis of lesions composed of these cell lineages.